Tangled the series. Queen for a day [videorecording (DVD)] (Tangled: the series., 2017)
The fate or Corona hangs in the balance when everyone's favorite 'barefoot princess' faces the ultimate test as Queen for a Day. Left in charge during her parents' absence, Rapunzel thinks she's got this - until every royal decision she makes backfires!